Chambres en souffrance : révéler la parole des artistes et des femmes victimes de violences à travers l’espace intime - Adélie Le Guen (Les Cahiers de l'École du Louvre)
How did female artists extract violence from the space of a bedroom? Explaining women and their involved and complex wounds was the primary aim of artists who wished to examine this intimate setting and the psychoanalytical and political expressions that it expressed. The bedroom, an open stage, is a favourite venue in the reconstruction of traumatic events, experienced by the artists themselves or by women they feel close to. Virginia Woolf discussed this enclosed space, which, like their own bodies, women could not freely avail themselves of; this room – in which they lacked the freedom to love in accordance with their choices, to create as they wished, or just to be alone – represents subordination, abuse, wounds. By analysing key works – reflections of militant contexts – from the 1970s to the present day, an analysis is made of the problems raised by women artists: dangers or violence faced by women, female students, prostitutes and young children.